Decreased amplitude of left ventricular posterior wall motion with notch movement to determine the left posterior septal accessory pathway in Wolff-Parkinson-White syndrome. Issue 6 (1st December 1999) - Hina, K; Murakami, T; Kusachi, S; Hirami, R; Matano, S; Ohnishi, N; Iwasaki, K; Kita, T; Sakakibara, N; Tsuji, T
Abstract : OBJECTIVE: To determine preoperatively, by analysing asynchronous left ventricular wall motion, whether to approach through the right ventricle or the left ventricle when carrying out catheter ablation of the accessory pathway in Wolff-Parkinson-White syndrome, especially in patients with the pathway located on the septum. METHODS: 73 patients with manifest Wolff-Parkinson-White syndrome who underwent successful catheter ablation were studied. Location of accessory pathway was classified as right ventricular side : right anterior paraseptum, right anterior, right lateral, right posterior, anterior septum, midseptum, right posterior septum; left ventricular side : left posterior septum, left posterior, left lateral, left anterior. Asynchronous systolic wall motion was analysed by cross sectional echocardiography. RESULTS: Echocardiography showed that the amplitude of left ventricular posterior systolic wall motion was reduced when the pathway was located on the left ventricular side as opposed to the right ventricular side (mean (SD), 11.1 (1.7) v 12.9 (1.1) mm, p < 0.001), especially in patients with left posterior septal accessory pathway (9.7 (0.8) mm). There were no overlapping values between the left posterior septal accessory pathway and the right ventricular side accessory pathway. Posterior wall notch motion was observed in all patients with a left posterior septal accessory pathway (9/9), but not at all in patients with pathways located on the right ventricular side of the septum. In patients with a septal accessory pathway, an ECG algorithm provided poor information (relatively low sensitivity, specificity, and predictive value) for determining whether the subsite faced either the left (left posterior septum) or the right ventricle (anterior septum, midseptum, right posterior septum). CONCLUSIONS: Decreased amplitude of left ventricular posterior wall motion with notch movement is an important finding for accessory pathways located on the left posterior septum. These findings provided clinically useful information for determining whether to approach catheter ablation from the right or the left ventricle.